Escalation of Anti-Party Sentiment Among First-Time Voters in Cilegon City - Ria Amelia; Yeby Ma'asan Mayrudin; Azka Abdi Amrurobbi (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This paper explores young people’s understanding of political parties amid a crisis of legitimacy and public trust. Political parties are essential pillars of a democratic state, serving crucial functions as instruments of democracy and channels for public aspirations. However, political parties today face a severe trust crisis from society. This crisis stems from widespread disappointment toward politicians, parties, and their elites, which has fueled anti-party sentiment, particularly among young people. The purpose of this paper is to examine the issue of anti-party sentiment and its impact on democratization and the weakening legitimacy of political parties. The phenomenon is analyzed using the theory of anti-party sentiment, which identifies several forms of sentiment among young people, namely the denial of party, the selective acceptance of the party system, the selective rejection of the party system, and the redundancy of party. This study employs a qualitative method with a phenomenological approach following Creswell’s framework. Through this phenomenological approach, the author investigates in depth the experiences of informants who exhibit anti-party sentiment among young people in the era of political digitalization in Cilegon, using interviews and objective observations. This paper discusses how society perceives and interprets the role of political parties in their everyday lives. Keywords: Political party, oligarchy, young people, anti-party sentiment.